Analysis Of The Role Of People's Business Credit (KUR), Exchange Rate, And Exports, And Their Relationship To GRDP Of North Sumatra 2016 – 2020 - Hasyim Hasyim; Monalisa Lumbantobing; Henny Mawarta Siregar; Nur Indah Melani Aruan (SEAN Institute, 2023)
This research aims to analyze the role of People's Business Credit (KUR), foreign exchange rates, and exports in relation to the Gross Regional Domestic Product (GRDP) of North Sumatra during the period from 2016 to 2020. This study is important to understand the impact of these variables on economic growth and the potential development of key sectors in the region. This research utilizes a quantitative approach and secondary data obtained from relevant agencies and financial institutions. The collected data includes the value of KUR, foreign exchange rates, exports, and the GRDP of North Sumatra. The analysis results indicate a positive relationship between KUR, foreign exchange rates, exports, and the GRDP of North Sumatra. KUR plays a crucial role in improving financial access for micro, small, and medium enterprises (MSMEs) in the region, which in turn contributes to economic growth. Foreign exchange rates also influence the GRDP as they can affect the competitiveness of export and import products. Moreover, exports have a positive impact on the GRDP by increasing income and driving related economic sectors.